Crowdfunding as a formula for the financing of projects: an empirical analysis - Fondevila-Gascón, Joan-Francesc (2015)
Crowdfunding offers enormous possibilities for marketing and communication, given that it facilitates the circulation of new projects, generates audiences and creates a loyal social base. Nevertheless, experiences of crowdfunding can be diverse. The aims of this investigation are threefold; to analyse crowdfunding platforms in Spain by means of quantitative and qualitative research methods (descriptive and relational); carry out a comparative study of the efficiency index of crowdfunding campaigns for profit-making projects as compared with campaigns raising money for social causes; and to propose good practice guidelines listing the key points of a successful campaign. The results obtained indicate that the percentage of successful profit-making campaigns is no higher than that for charitable ones, and that compliance with the key points in the proposed good practice guidelines is more likely to result in a successful crowdfunding campaign.